Developments in regulatory regimes: An Anglo-German comparison on telecommunications, energy and rail - Dominik Böllhoff (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2002)
The liberalisation and privatisation of network utilities lead to the establishment of regulatory regimes. On the national level, regulatory regimes not only include a highly visible single regulatory body, they also combine three institutions: a sector-specific regulatory agency, a ministry and a competition authority. These three organisations are the central institutions within the regime. They share competencies and interact with each other to steer national utility sectors.From a comparative administrative research perspective, this article explores developments in utility regulatory regimes in Britain and Germany, especially focussing on telecommunications, energy (electricity and gas) and rail. The goal is to show that regulatory regimes are not stable entities, but that there are 'post-reform changes' which result in redesigning regimes over time. To create and correct markets, there are ongoing modifications of regimes aimed at coping with the sector-specific changes.With respect to economic regulatory competencies of regulatory regimes, cross-country and cross-sectoral institutional dynamics are explored. This article reveals that there are general converging trends in Britain's regulatory regimes and partial convergence in Germany's regimes. An Anglo-German cross-country comparison shows some similarities; for example, on the role of ministries within the regimes. However, the developments in the regimes do not result in overall cross-sectoral convergence. There is continuing divergence in the regulatory regimes.
Keywords: 330; Telekommunikationspolitik; Elektrizitätspolitik; Eisenbahnpolitik; Institutioneller Wandel; Vergleich; Großbritannien; Deutschland